ANALISIS PENGARUH SUHU DAN WAKTU PADA SENSOR ECT TERHADAP PERFORMA ENGINE MANAGEMENT SYSTEM PADA MESIN TOYOTA AVANZA 2NR DALAM KONDISI STATIONER - Muhaimin Rifdi Hamdi; Agus Adi Nursalim; Fikri Ulul Albab (Universitas Islam Al-Ihya Kuningan, 2023)
Engine Management System is a system used to regulate the proper air-fuel mixture, accurate ignition timing, and control other engine systems based on the conditions and workload of the vehicle. The EMS components consist of sensors, ECU, and actuators. This research aims to identify the influence of temperature and time variations on the Engine Coolant Temperature sensor on the performance of the EMS in the Toyota Avanza 2NR engine. The experimental method was employed, conducting experiments under various temperature conditions 30°C to 80°C and working durations 3 to 18 minutes to measure parameters such as Engine RPM, Injection Time, Ignition Timing, Intake Air Temperature, Engine Load, and Air Intake. Based on the research findings and data analysis, it can be concluded that there is a significant impact of temperature and working time on the ECT sensor's effect on the performance of the Engine Management System at idle speed. As the temperature increases, there is a gradual decrease in Engine Load from 42% to 34%, Engine RPM from 1291.85 to 601.77 RPM, Injection Time from 3.5 m/s to 2.3 m/s, and Air Intake from 4.93 g/s to 1.51 g/s. The Intake Air Temperature remains relatively stable around 29°C to 36°C. Furthermore, there are variations observed in the Ignition Timing parameter to ensure proper combustion and optimal engine performance.